A novel bicoumarin-based multifunctional fluorescent probe for naked-eye sensing of amines/ammonia. Issue 13 (17th March 2020) - Zhang, Ensheng; Hou, Xiufang; Yang, Hua; Zou, Yong; Ju, Ping
Abstract : A novel bicoumarin-based fluorescent probe ( apbis-c ) for amine/ammonia sensing and its potential applications were revealed. Abstract : A novel bicoumarin-based fluorescent and colorimetric probe 7, 7′-(acetoxy)-3, 3′-( p -phenylene)bis(coumarin) ( apbis-c ) for the highly sensitive detection of amines/ammonia in solution and ammonia vapor in air was constructed for the first time by using the Perkin reaction between 1, 4-phenylenediacetic acid and 2, 4-dihydroxybenzaldehyde. Instant color changes and real-time fluorescence responses were observed for apbis-c after treatment with different primary and secondary aliphatic amines as well as ammonia in THF/DMSO. Paper-based sensors were prepared by simply depositing apbis-c on filter paper and used in the highly selective and sensitive detection of ammonia vapor in air with an experimental detection limit of 6.85 ppm (the calculated LOD is 0.71 ppm). A plausible mechanism for the fluorescence and colorimetric responses of apbis-c to ammonia was proposed based on 1 H NMR study and DFT calculations. In addition, practical studies revealed that apbis-c could be used for the preparation of fluorescent invisible ink, food spoilage indicators and naked eye sensors for lysine/arginine.